A divisibilidade no Ensino Fundamental - Valentim, Erivan Sousa (2017)
The purpose of this work is to realize an approach about multiples and divisors, in- cluding the least common multiple and the greatest common divisor, owing to the diﬃculty that students feel when they faced with such content in basic education, aiming at a better understanding about it and an improvement in the learning of le- arners. The suggestion was applied in an 8th grade class at the Joaquim Limeira de Queiroz Agricultural Technical School, in the city of Puxinan˜ a - PB, in March 2017. They were addressed the deﬁnitions of multiples, divisors, prime numbers and the least common multiple and the greatest common divisor, and it was applied activities such as: bingo of the divisors, the sum of the magic square and the construction of the Sieve of Eratosthenes. Finally, we carried out an evaluation exercise with the objective of analyzing if the results regarding the content and the activities previously proposed were satisfactory.